Globalisasi, liberalisasi, dan daya saing sektor pertanian - Hadiwigeno, Soetatwo (Economic Journal of Emerging Markets, 2016)
As we know that the globalization and liberalization process have impact in many aspects, economic, and social problems. Indonesia as a developing country will get because of its low competitiveness. The government must develop an appropriate policy to solve this problem.